New possibilities in pharmacotherapy for the heart failure with reduced ejection fraction treatment in patients with recent deterioration - I. V. Gribkova (Рациональная фармакотерапия в кардиологии, 2024)
Heart failure with reduced ejection fraction (HFrEF) is a public health issue, because some patients, despite using standard treatment, still develop worsening heart failure. The risk of adverse outcomes is especially high in patients who require readmission or emergency care on an outpatient basis. They need a new type of treatment. Vericiguat is the first oral soluble guanylate cyclase stimulator approved for the treatment of adults with symptomatic HFrEF. This article summarizes the main results of the use of this drug. The effectiveness and tolerability of vericiguat, the dependence of its action on the initial state of patients (the presence of coronary heart disease, atrial fibrillation, renal failure, the level of N-terminal pro b-type natriuretic peptide (NT-proBNP) and the duration of the period after hospitalization) are considered. It is reported that the use of the drug reduces the risk of hospitalization for worsening HF and death from cardiovascular diseases in all patients with HFrEF, regardless of the considered baseline parameters, but does not significantly affect the patients’ quality of life of. These results may be useful in determining the place of vericiguat in the management of a growing population of patients with chronic HFrEF who have experienced recent deterioration despite receiving standard therapy.